(3eaghe GdbQUfI GdHMQjI h eOi JCKjQ GdbQUfI GdUheGdjI Ydi CMcGe GdbGfhf GdOhdj HTCf GdbQUfI (B/s - (3ShjOj(B: (3Sja ZGfe(B..s ((3OHj (B:s (3eQcR GdHMhK h GdOQGSGJ HCcGOjejI TQWI OHj(B:s, 2013)
(3jSJYQV GdHMK CMcGe GdbQUfI GdHMQjI GdOhdjI heaghegG GdbGfhfj(B: (3hef NdGd JMdjd bVjI GdbQUfI GdUheGdjI Jecf ef deS hGMO ef Cge GdCSHGH GdbGfhfjI GdJj QHeG bO Jchf GdSHH aj JaGbe MLe GdbQUfI GdHMQjI(B. (3hjJeKd Pdc GdSHH aj Gdeaghe GdbGfhfj GdeYJeO ddbQUfI GdHMQjI GdOhdjI GdefUhU Ydjg aj GJaGbjI GdCee GdeJMOI dbGfhf GdHMGQ dYGe (B1982(3e(B.(3hjQcR GdHMK Ydi JMdjd YfGUQ Gdeaghe GdbGfhfj ddbQUfI GdHMQjI hJhVjM eOi JCKjQgG Ydi JaGbe GdLQjeI(B: (3ceG Cfg jJWQb ddHMK ai JMdjd GdbjeI GdbGfhfjI dbQGQGJ eLdS GdCef GdOhdj ddCee GdeJMOI HTCf GdbQUfI GdHMQjI GdUheGdjI hHjGf eOi JCKjQgG aj JZjjQ eaghe GdbQUfI GdHMQjI(B..s
"(3HMK Ydej eMce hefThQ aj eLdI GdCef h GdbGfhf(B: (3CcGOjejI TQWI OHj(B: (3jfGjQ (B2010" -- (3U(B. (3GdYfhGf(B..s
(3EUOGQGJ bGfhfjI(B..s
Keywords: (3GdbQUfI GdHMQjI (B((3bGfhf Ohdj(B).s; (3GdbQUfI GdHMQjI(B..s; (3GdbQUfI GdHMQjIs